High-Frequency Ultrasonography Imaging: Anatomical Measuring Site as Potential Clinical Marker for Early Identification of Breast Cancer-Related Lymphedema - Ivana Klarić-Kukuz; Danijela Budimir Mršić; Antonela Matana; Blaž Barun; Jure Aljinović; Maja Marinović-Guić; Ana Poljičanin (Biomedicines)
Background/Objectives: Accurate diagnosis of breast cancer-related lymphedema remains a clinical challenge. This study evaluated the diagnostic utility of ultrasound in detecting early lymphedema compared to conventional criteria, including the International Society of Lymphology staging and limb volume measurements. Methods: In this retrospective cross-sectional study, 68 female participants with unilateral breast cancer, who had completed cancer treatment at least six months before study enrolment, underwent both ultrasonographic assessment and standard limb circumference measurements. Ultrasound was performed bilaterally at five standardized anatomical sites. Sonographic parameters included assessment of cutaneous and subcutaneous thickness and echogenicity. Clinical staging and symptom profiles were assessed using ISL criteria and a structured questionnaire. Volume status was determined by relative volume change (RVC). Results: Among 68 participants, 36 were classified as ISL stage 0 and 32 as ISL stage II, 30 had RVC < 5%, while 38 had RVC ≥ 5%. Advanced stages were associated with older age. Multivariate analysis identified increased skin thickness at the medial upper arm cutis as significantly correlated with RVC ≥ 5% (OR 1.49, 95% CI: 1.01–2.21, p = 0.047). A similar trend was observed at the medial forearm (OR 1.3 (95% CI: (0.99, 1.71))). Conclusions: This study highlights ultrasound’s potential for early breast cancer-related lymphedema detection, especially in patients with minimal volume changes where conventional methods fall short. Increased cutaneous thickness in the medial upper arm emerged as a sensitive marker of early disease, while subcutaneous thickness and echogenicity may reflect in advanced stages. This distinction underscores the clinical value of cutaneous thickness as a potential clinical key marker for early lymphedema detection, emphasizing the need for standardized protocols and defined thresholds to guide timely interventions.